Berberine Ameliorates Subarachnoid Hemorrhage Injury via Induction of Sirtuin 1 and Inhibiting HMGB1/Nf-κB Pathway - Zhang, Xiang-Hua; Peng, Lei; Zhang, Jing; Dong, Yi-Peng; Wang, Cheng-Jun; Liu, Cang; Xia, Da-Yong; Zhang, Xiang-Sheng (Frontiers in Pharmacology, 2020)
Excessive cerebral inflammation plays a key role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). Berberine, an isoquinoline alkaloid isolated from Chinese herb Coptis chinensis, possesses anti-inflammatory and neuroprotective effects. Here we evaluated the beneficial effects of berberine against SAH-induced inflammatory response and the subsequent brain injury. Our data showed that berberine treatment significantly inhibited microglia activation and proinflammatory cytokines release. Concomitant with suppressed cerebral inflammation, berberine mitigated the subsequent brain injury as demonstrated by improved neurological behavior, reduced brain edema, and decreased apoptosis. Moreover, berberine significantly inhibited high mobile group box 1 (HMGB1)/ nuclear factor-κB (Nf-κB)-dependent pathway and enhanced sirtuin 1 (SIRT1) expression after SAH. Treatment with ex527, a selective SIRT1 inhibitor, reversed berberine-induced SIRT1 activation and inhibitory effects on HMGB1/Nf-κB activation. In addition, ex527 pretreatment abated the anti-inflammatory and neuroprotective effects of berberine on SAH. Taken together, these findings suggest that berberine provides beneficial effects against SAH-triggered cerebral inflammation by inhibiting HMGB1/Nf-κB pathway, which may be modulated by SIRT1 activation.